2018
DOI: 10.1037/cou0000298
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Racism Scales for Asian American Men: Scale development and psychometric properties.

Abstract: The Gendered Racism Scales for Asian American Men (GRSAM) was developed to assess the frequency and stress level of gendered racism perceived by Asian American men. The development of the new measure was grounded in the Intersectional Fusion Paradigm. This paradigm explains individuals' experiences of discrimination based on unique combinations of multiple interlocking identities that individuals experience simultaneously. In mixed samples of college students and community adults, GRSAM's factor structure as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 49 publications
2
39
2
Order By: Relevance
“…Wong, Wang, and Farmer’s (2018) dynamic paradigm of ethnic culture, for example, examines contextual and temporal influences that impact ethnic culture, emphasizing its “fragmented, subjective, antiessentialist, and performative nature” (p. 1). Measures designed to transcend additive and multiplicative approaches to quantitative intersectional research include the Gendered Racial Microaggressions Scale for Black women (Lewis & Neville, 2015) and Asian American women (Keum et al, 2018), the Black Men’s Experiences Scale (Bowleg et al, 2016), and the Gendered Racism Scales for Asian American Men (Liu, Wong, Maffini, Mitts, & Iwamoto, 2018).…”
Section: Five: Enrich Intersectionality In Vocational Psychology Schomentioning
confidence: 99%
“…Wong, Wang, and Farmer’s (2018) dynamic paradigm of ethnic culture, for example, examines contextual and temporal influences that impact ethnic culture, emphasizing its “fragmented, subjective, antiessentialist, and performative nature” (p. 1). Measures designed to transcend additive and multiplicative approaches to quantitative intersectional research include the Gendered Racial Microaggressions Scale for Black women (Lewis & Neville, 2015) and Asian American women (Keum et al, 2018), the Black Men’s Experiences Scale (Bowleg et al, 2016), and the Gendered Racism Scales for Asian American Men (Liu, Wong, Maffini, Mitts, & Iwamoto, 2018).…”
Section: Five: Enrich Intersectionality In Vocational Psychology Schomentioning
confidence: 99%
“…Higher acculturation predicted greater conflict from the "success, power, and competition" patriarchal male role norm (E. J. Kim et al, 1996) and greater general masculine gender role stress, and higher individualism (a European American interpersonal orientation) predicted greater gendered racism-related stress (T. Liu et al, 2018). Interestingly, the association between acculturation and gender role conflict from restrictive emotionality was negative in a study using a unidimensional measure of acculturation (E. J.…”
Section: Acculturationmentioning
confidence: 99%
“…Specifically, racial immersion and resistance (W. M. Liu, 2002) and Asian values (W. M. Liu & Iwamoto, 2006) positively predict all domains of gender role conflict. In addition, Asian American male identity centrality was positively correlated with masculine gender role stress, and collectivism was positively correlated with gendered racism-related stress (T. Liu et al, 2018). Examining Asian American men's racial identity, W. M. Liu (2002) found that racial identity dissonance (i.e., struggle with integrating mainstream and heritage cultures) predicted greater gender role conflict and internalization (i.e., successful integration) positively predicted both endorsement of traditional male role norms and gender role conflict (W. M. Liu, 2002).…”
Section: Kyler-mentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging research suggests that Asian American men (AAM) who experience gendered racism are more likely to develop depressive symptoms (Liu et al, 2018). AAM are uniquely marginalized by being stereotyped as effeminate, romantically/sexually undesirable, uncharismatic, and lacking leadership quality, among other racialized qualities (Liu et al, 2018).…”
Section: The Present Studymentioning
confidence: 99%